FENOMENA TENTARA BAYARAN DAN KEMUNGKINAN IMPLEMENTASINYA DI INDONESIA - Marnani, Christine Sri (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
The phenomenon of using mercenaries in armed conflicts has been a controversial issue around the around the world since BC. However, until now the phenomenon still exists, especially since Russia's attack on Ukraine in 2022. This global phenomenon raises a question, "how is the phenomenon of mercenaries in the perspective of the State Defense System ? And what are the implications of the implementation of mercenaries in the perspective of the National Defense System?” This research uses the theory of Geostrategy, National Security, State Defense System, and the Concept of State Defense as the basis of analysis. The researcher will analyze the concept of State Defense in the Indonesian State Defense System with parameters of the Basic Values of State Defense, namely 1) love for the country, 2) aware of the nation and state, 3) believe in Pancasila as the state ideology, 4) willing to sacrifice for the nation and state, 5) have the initial ability to defend the country. The research method uses a qualitative approach based on literature data sources. The results of the research analysis are that, based on the Indonesian State Defense System, the presence of mercenaries has not become a significant phenomenon in armed conflicts. Citizens who will defend their country are Indonesian citizens who have met the requirements of the Basic Values in State Defense. The implication of the use of mercenaries in Indonesia is that the state will lose control of its military power. Keywords: mercenaries, implementation in Indonesia, armed conflict, state defense, national defense system.